2022
DOI: 10.1177/23259671221088331
|View full text |Cite
|
Sign up to set email alerts
|

Medial and Lateral Posterior Tibial Slope in the Skeletally Immature: A Cadaveric Study

Abstract: Background: An increased posterior tibial slope (PTS) results in greater force on the anterior cruciate ligament (ACL) and is a risk factor for ACL injuries. Biomechanical studies have suggested that a reduction in the PTS angle may lower the risk of ACL injuries. However, the majority of these investigations have been in the adult population. Purpose: To assess the mean medial and lateral PTS on pediatric cadaveric specimens without known knee injuries. Study Design: Cross-sectional study; Level of evidence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Although this number deviates by roughly 1° to 1.5° from the adult normal PTSA, it is important to note that this study had a relatively small sample size with a high degree of variability based on the relatively large standard deviation. 2 Furthermore, we observed a mean PTSA in our control group of 7.3°± 4.3°, which was more consistent with the normal range we used. In another adult study, a PTSA ≥12° was associated with a 3.1 times greater risk of ACL reconstruction (ACLR) graft rupture compared with a slope <12°.…”
Section: Discussionsupporting
confidence: 88%
“…Although this number deviates by roughly 1° to 1.5° from the adult normal PTSA, it is important to note that this study had a relatively small sample size with a high degree of variability based on the relatively large standard deviation. 2 Furthermore, we observed a mean PTSA in our control group of 7.3°± 4.3°, which was more consistent with the normal range we used. In another adult study, a PTSA ≥12° was associated with a 3.1 times greater risk of ACL reconstruction (ACLR) graft rupture compared with a slope <12°.…”
Section: Discussionsupporting
confidence: 88%
“…Elyasi et al [ 42 ] showed that increased posterior tibial slope can induce an anterior translation of the tibia with respect to the femur, which raises a concern about whether it can increase the strain of the anterior cruciate ligament (ACL) and result in a higher risk of ACL rupture. Anchustegui et al [ 43 ] reported that an increased posterior tibial slope is an independent risk factor for ACL graft rupture, with a critical threshold of 12 degrees. Excessive tibial slope increases the posterior space, leading to a loose posterior cruciate ligament (PCL) in cruciate-retaining implants [ 35 ].…”
Section: Discussionmentioning
confidence: 99%